Epidemiology and practice patterns for male breast cancer compared with female breast cancer in Japan. (1st July 2020) - Ishii, Taisuke; Nakano, Eriko; Watanabe, Tomone; Higashi, Takahiro
Abstract: Background: The incidence of male breast cancer (MBC), although rare, has shown an increase. However, the current epidemiology of and practice patterns for MBC remain unclear. This study evaluated the characteristics and care patterns for MBC compared with female breast cancer (FBC) in Japan. Methods: Using the National Database of Hospital‐Based Cancer Registries (HBCR) linked to the Diagnosis Procedure Combination data, we analyzed newly diagnosed breast cancer cases between January 2012 and December 2015 at participating hospitals in a large quality‐of‐care monitoring project. We employed logistic regression models to assess cancer treatment differences between MBC and FBC in patients who were indicated for adjuvant radiation therapy and neo‐adjuvant/adjuvant chemotherapy. Results: Of 142, 636 breast cancer patients, 870 (0.61%) were MBC patients. At diagnosis, the mean age of MBC patients was 10 years older than FBC patients (70 vs 60 years; P  < .001). Advanced‐stage cancer was more frequently observed in MBC than in FBC (stage III/IV 18.9%/6.1% vs 10.6%/5.2%). Despite this, MBC patients were less likely to receive adjuvant radiation therapy and neo‐adjuvant/adjuvant chemotherapy. Gender was an independent treatment determinant factor for chemotherapy decisions. Conclusion: MBC patients were older and had higher stages of cancer than FBC patients at diagnosis, but received suboptimal treatment. Abstract : Male breast cancer was rare cancer and diagnosed with more advanced stage than female breast cancer. However, male breast cancer patients were received suboptimal adjuvant therapy, including radiation and chemotherapy despite of guidelines which recommend the same indication and regimen to both male and female breast cancer.